“Doing it for my family”: examining when and how family motivation hinders creativity of hospitality employees by shaping job-perception - Isac, Nicoleta; Badshah, Waqar; Ahmad, Bashir; Qammar, Ahmad; Kalyar, Masood Nawaz; Isac, Nıcoleta (Emerald Group Publishing Ltd., 2024)
Purpose – This study explores the relationship between family motivation and employee creativity. It examines the way family motivation shapes employees’ job perceptions, specifically examining the mediating roles of job instrumentality and job meaningfulness detachment. Additionally, the study explores the moderating effect of family financial pressure. Design/methodology/approach – The data were collected in three waves over six months from 382 employees in the Turkish hospitality industry. The Warp PLS 7.0 software was utilized for data analysis using partial least squares structural equation modeling (PLS-SEM). Findings – The results indicate that family motivation significantly influences job instrumentality and job meaningfulness detachment, which subsequently reduce employee creativity. Moreover, family financial pressure moderates the relationship between family motivation and job perception, thereby amplifying its effects. Research limitations/implications – This study highlights that organizations should minimize ambiguity and complexity, create a psychologically safe environment, align incentives with creativity, address conflicts between short-term gains and long-term projects and support work-life balance in the hospitality industry. This can enhance employee creativity, satisfaction and retention.
Keywords: Family motivation; Creativity; Job instrumentality; Meaningfulness detachment; Hospitality